Multiple Vaccines and Strategies for Pandemic Preparedness of Avian Influenza Virus - Hai Xu; Shanyuan Zhu; Roshini Govinden; Hafizah Y. Chenia (Viruses, 2023)
Avian influenza viruses (AIV) are a continuous cause of concern due to their pandemic potential and devasting effects on poultry, birds, and human health. The low pathogenic avian influenza virus has the potential to evolve into a highly pathogenic avian influenza virus, resulting in its rapid spread and significant outbreaks in poultry. Over the years, a wide array of traditional and novel strategies has been implemented to prevent the transmission of AIV in poultry. Mass vaccination is still an economical and effective approach to establish immune protection against clinical virus infection. At present, some AIV vaccines have been licensed for large-scale production and use in the poultry industry; however, other new types of AIV vaccines are currently under research and development. In this review, we assess the recent progress surrounding the various types of AIV vaccines, which are based on the classical and next-generation platforms. Additionally, the delivery systems for nucleic acid vaccines are discussed, since these vaccines have attracted significant attention following their significant role in the fight against COVID-19. We also provide a general introduction to the dendritic targeting strategy, which can be used to enhance the immune efficiency of AIV vaccines. This review may be beneficial for the avian influenza research community, providing ideas for the design and development of new AIV vaccines.